The role of heat transfer resistance of a window in formation of resulting temperature at the boundary of habitable space in a room - E. G. Malyavina; S. S. Landyrev (Vestnik MGSU)
Introduction. According to current regulations, values of required heat transfer resistance of external enclosing structures must comply with the purpose of a building, a structure itself and the number of degree days in a heating period. This technique applies to all external enclosing structures, including windows. However, windows have greatly lower heat transfer resistance than solid envelopes. Therefore, windows have a greater effect on temperature than solid envelopes at the boundary of habitable space in a room.Materials and methods. The resulting temperature at the boundary of habitable space is lowest when outdoor temperature is lowest, or when temperature is lowest for five days in a raw. It has been found out that during such periods standards of resulting temperature are not met. A regression curve, made using the least squares method, is presented; it describes the relationship between t592 and the heating season degree-day (HSDD) for nursery and junior groups of preschool institutions in 30 cities of the Russian Federation. Some points are below the trendline. It is for such cities that it is proposed to take into account not only the HSDD, but also t592 when standards are set for resistance of windows to heat transfer.Results. Resulting temperatures at the boundary of habitable space in a room are determined. They show that optimal requirements for resulting temperature are never met, while acceptable requirements are met for all values of heat transfer resistance of windows and exterior walls, even if resistance to heat transfer is normalized. As for the local asymmetry of resulting temperature, its standards are also met at all times. Values of resistance of windows to heat transfer are calculated to find those that correspond to optimal resulting temperatures at the boundary of habitable areas of rooms for nursery and junior groups at preschool institutions if basic values of resistance of exterior walls to heat transfer remain unchanged. In a large number of cases, values of resistance of windows to heat transfer greatly exceed the maximum value set by Construction Regulations 50.13330.Conclusions. If the choice of a large value of window width is only explained by aesthetic reasons, the window’s resistance to heat transfer must exceed 0.8 m2∙°С/W, despite higher costs of such windows.